ANALISIS PERBANDINGAN LAPORAN KEUANGAN SEBELUM DAN SETELAH PENERAPAN STANDAR AKUNTANSI BARU - Riko Mahesa; Ersi Sisdianto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The implementation of new accounting standards has a substantial impact on how information is presented, measured, and disclosed in the company's financial statements. This journal compares the company's financial statements before and after the adoption of new accounting standards, focusing on changes to revenue recognition, asset and liability measurement, and information disclosure. This analysis was conducted using a case study approach on several companies that implemented new accounting standards, as well as a comparison of financial statements prepared before and after the changes. The results of the analysis reveal significant changes to the measurement and presentation of the financialstatements, which affect the financialchoices made by those who use the financial Keywords: New Accounting Standards, Financial Statements, Comparison of Financial Statements, Revenue Recognition, Assets, Liabilities, Disclosure.